impact of kpis on processes productive industry: impact of kpis on processes productive industry - Chávez Salazar, Luis
The KPI (Key Performance Indicators)have great importance for the continuousimprovement of the productive processesthat are carried out within industries, workingas a metric to describe different patternsof behavior in them. It is important tohighlight that this study of the KPI’S in themanagement of productive processes showsa positive impact in any factory that appliescontinuously to the process. Thus, this paperevidences the diverse successful storiesand the importance of how the MiPymesshould include these metrics to add valueto their productive processes and decreasethe existing gap between them and the bigindustries.